2019
DOI: 10.21608/zjar.2019.40322
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Microbiological Proprieties of Some Meat Products in Sharkia Governorate, Egypt

Abstract: Meat and meat products differ in their physical and chemical properties depending on the characteristic of meat cuts, the additional material and the method of manufacture. The present investigation was planned to evaluate the physical and chemical quality for some types of local meat products, such as beef burger and luncheon, collected from local markets in Zagazig city, Sharkia Governorate, Egypt. Microbiological and physicochemical proprieties of nine meat products (3 samples of beef burger of Americana, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…Ash content of beef luncheon samples ranged between 3.15 and 4.22 % with a mean value of 3.43 %. The obtained ash content in the current study seems to be nearly similar to that specified by E.O.S, as well as with those detected by Ragab et al (2019) since they observed that ash content ranged from 3 to 5.49% with mean value 3.8%.…”
Section: Chemical Examination For Deterioration Criteria Of Examined supporting
confidence: 90%
See 1 more Smart Citation
“…Ash content of beef luncheon samples ranged between 3.15 and 4.22 % with a mean value of 3.43 %. The obtained ash content in the current study seems to be nearly similar to that specified by E.O.S, as well as with those detected by Ragab et al (2019) since they observed that ash content ranged from 3 to 5.49% with mean value 3.8%.…”
Section: Chemical Examination For Deterioration Criteria Of Examined supporting
confidence: 90%
“…Ragab et al (2019) mentioned that the moisture contents of luncheon samples from different companies ranged between 65.61 and 68.29 %.…”
mentioning
confidence: 99%
“…Fried fish had the greatest protein level, while fried chicken strips had the lowest. Average of protein content of grilled beef burger was comparable to results obtained by Ragab et al (2019 ) and lower than results reported by Juárez et al (2010). Protein mean value in fried fish was nearly like percentage obtained by Magawata and Ahmed (2014).…”
Section: Discussionsupporting
confidence: 66%
“…These results may be due to the stimulating effect of mushroom powder on bacterial growth and subsequent acidity development (Synytsya et al, 2009 andNowak et al, 2018). On the other hand, titratable acidity increased significantly (p ≤ 0.05) in all labneh treatments as the storage period progressed (Ragab, 2000 andBasiony et al 2017). While pH followed an opposite trend to acidity, the pH of labneh treatments gradually decreased during storage period.…”
Section: Chemical Compositionmentioning
confidence: 92%